Resilience of Micro, Small, and Medium Enterprise (MSME) Actors "Pasar Kamu" in the Development of Kampoeng Lama Tourism Village - Wallad, Annisa Utami; Tohani, Entoh; Basuki, Agus (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2025)
This research aims to describe the resilience of MSME actors through aspects of resilience, resilience abilities, and independence of MSME actors in developing “the Pekan Breakfast Karya Anak Muda” (Pasar Kamu) tourist village. This research uses a qualitative method with a phenomenological approach. Data were collected through observation, interviews, and documentation. This research ensures data validity through source, technical, and time triangulation. Data analysis included data collection, condensation, presentation, and conclusion drawing. The research results show that (1) “Pasar Kamu” MSME players utilize digital marketing training and community involvement to increase product exposure and strengthen commitment. With an efficient management system, stress management strategy, and collaboration with business actors and the government, they support the sustainability of tourist villages through continuous improvement. (2) MSME players manage emotions and make measured decisions by discussing, exercising, and self-reflecting with mentors. They avoid impulsive decisions with a policy of overnight sleep and team consultation. Optimism and empathy are driven by achievement celebrations, motivational books, and community support, while systematic analysis increases efficiency and profitability. (3) “Pasar Kamu” MSME players overcome operational challenges through cooperative loans, strategic location selection, and cooperative assistance for production capacity. They implement appropriate strategic planning and management systems and use data-based performance evaluation to support sustainable growth.